The Influence of Brand Image, Promotion, and Product Quality on Customer Loyalty at Starbucks Study on Starbucks Karawang Product Customers - Samutthana, Citta; Kristanto, Yudi; Rahayu, Tutik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research is motivated by the phenomenon of Starbucks Karawang which continues to compete in the coffee retail business, Head of Corporate Communication PT Mitra Adi Perkasa Tbk. (MAPI) said with brand awareness strong, Starbucks continues to improve its business and performance so that it remains afloat amidst high competition which not only comes from coffee, but also from other types of drinks. In facing this competition, Starbucks remains focused on customer satisfaction and strives to provide a greater variety of products and services by improving its brand image, promotion and product quality to increase customer loyalty. This research using quantitative methods with associative techniques was carried out in Starbucks Karawang with a population and sample of 100 Starbucks customers with data collection techniques using questionnaires. The research results show that there is an influence between Brand Image (X1), Promotion (X2), and Product Quality (X3) on Customer Loyalty (Y) of 73.4%, meaning that 73.4% of the variation in Customer Loyalty can be explained by variations in Brand Image (X1), Promotion (X2), and Product Quality (X3), the remaining 26.6% is determined by other factors outside Brand Image (X1), Promotion (X2), and Product Quality (X3)